Corn or sorghum grain in growing-finishing rations (with and without added copper, Vitamin E, Biotin or Aureo SP-250) - Koch, B.A.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Pigs fed corn gained faster than those fed sorghum grain in one trial. The reverse was true in a second trial. Overall average daily gain figures were almost identical (1.67 lbs. per day for corn; 1.65 lbs. per day for sorghum). Average feed efficiency favored corn slightly (3.03 to 3.10). Adding 250 ppm copper to the diet significantly increased weight gain in one of five trials. Adding either vitamin E, biotin, or Aureo SP-250 did not significantly increase average daily gain or improve feed efficiency. Barrows gained 15% faster than gilts. Crossbred pigs gained 8% faster than the average of all purebreds.
Swine Industry Day 1970 is known as Swine Day, 1970
Keywords: Swine; Corn; Sorghum grain; Growing-finishing rations; Copper; Vitamin E; Biotin; Aureo SP-250